(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
The article discusses the problems resolution in the continuing formation of Mathematics teachers of the Basic Education. It investigates the problems resolution methodology as a didactic resource in the construction of the mathematical knowledge during the continuing formation of 24 Mathematics teachers in service. The continuing formation has enabled the research about the problems resolution methodology and the development of reflective didactic actions, linking up theory with practice in the problems resolution, contributing to the ressignification of mathematical knowledge and of the problems resolution methodology in the pedagogical practice of teachers from public schools.